Implementasi Strategi Pembelajaran Gallery of Learning untuk Meningkatkan Hasil Belajar Peserta Didik pada Mata Pelajaran Bahasa Arab Kelas XI IPA MAN 4 Sleman - Ulfah Hasanah (Edulab : Majalah Ilmiah Laboratorium Pendidikan, 2018)
This study aims to determine the implementation of Arabic learning using the Gallery of Learning strategy and is there an increase in student learning outcomes after the Gallery of Learning learning strategy is applied. This research model uses a quasi-experimental design model (Quasi Experiment) with test techniques (pre-test and post-test), observation, interviews, and documentation. Data analysis to test the hypothesis proposed using the "t" test through the SPSS 16.0 program as well as the validity test, reliability test, normality test, and homogeneity test. The analysis shows that the implementation of Arabic learning begins with the teacher explaining the material to be learned, then students are divided into 8 groups. The teacher explains the task of the group to discuss the material that has been determined and write the results on paper and put on top of the sponati and make a gallery. Then each group shares an assignment to tour the gallery to find out other material and maintain the gallery to explain the contents of the material to students who visit the gallery. The end of the activity is a reflection and conclusions together on what has been learned. After the implementation of the strategy, it was found that there was no significant increase in student learning outcomes using the Gallery of Learning learning strategy in class XI IPA 1 MAN 4 Sleman. Based on the results of the "t" test, the value of Sig. (2-tailed) = 0.195> 0.025, then on the basis of Independent Sample t-Test decision making, it is evident that there is a difference in influence between the average experimental group and the control group. However, it is not significant. The results of this analysis can be concluded that the Gallery of Learning learning strategy cannot significantly improve student learning outcomes in Arabic subjects in class XI IPA MAN 4 Sleman. Abstrak Penelitian ini bertujuan untuk mengetahui pelaksanaan pembelajaran bahasa Arab menggunakan strategi pembelajaran Gallery Of Learning dan adakah peningkatan hasil belajar peserta didik setelah diterapkan strategi pembelajaran Gallery Of Learning. Model penelitian ini menggunakan eksperimen model desain eksperimen kuasi (Quasi Eksperimen) dengan teknik tes (pre-test dan post-test), observasi, wawancara, dan dokumentasi. Analisis data untuk menguji hipotesis yang diajukan menggunakan uji “t” melalui program SPSS 16.0 serta uji validitas, uji reliabilitas, uji normalitas, dan uji homogenitas. Hasil analisis menunjukkan bahwa pelaksanaan pembelajaran bahasa Arab diawali dengan guru menjelaskan materi yang akan dipelajari, kemudian siswa dibagi menjadi 8 kelompok. Guru menjelaskan tugas kelompok untuk berdiskusi tentang materi yang telah ditentukann dan menuliskan hasilnya di kertas dan ditempelkan di atas sponati dan membuat sebuah galeri. Kemudian setiap kelompok berbagi tugas untuk berkeliling galeri mencari tahu materi yang lain dan menjaga galeri untuk menjelaskan isi materi kepada siswa yang berkunjung ke galerinya. Akhir kegiatan diadakan refleksi dan menyimpulkan bersama terhadap apa yang telah dipelajari. Setelah diterapkannya strategi tersebut diketahui adanya peningkatan yang tidak signifikan pada hasil belajar siswa menggunakan strategi pembelajaran Gallery of Learning di kelas XI IPA 1 MAN 4 Sleman. Berdasarkan hasil uji “t”, nilai Sig.(2-tailed)=0.195>0.025, maka dengan dasar pengambilan keputusan Independent Sample t-Test, terbukti terdapat perbedaan pengaruh antara rata-rata kelompok eksperimen dan kelompok kontrol. Namun, tidak signifikan. Hasil analisis tersebut dapat disimpulkan bahwa strategi pembelajaran Gallery of Learning tidak dapat meningkatkan hasil belajar peserta didik secara signifikan pada mata pelajaran bahasa Arab kelas XI IPA MAN 4 Sleman. Kata Kunci: Strategi Pembelajaran Gallery of Learning, Hasil Belajar Siswa